Effects of electronic blackmail as a punishment between Imami jurisprudence and Iraqi law - Islamic Reza Yasser Qutaish . Abdul-Ridha Nasir Sabet Al-Bahadli ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The study dealt with the issue of the penalty of electronic extortion in the Imami and Iraqi legal jurisprudence, and it showed that the crime of electronic extortion, even if it was one of the new crimes in our contemporary world, which appeared after the emergence of technology, and electronic extortion is one of the crimes that corrupt morals in society, but rather includes an attack on money and honor and has serious effects on the The individual and society, and electronic blackmail are among the crimes that the ancient jurists were not exposed to in their books. But because the final Islamic Sharia is a complete way of life, it did not leave anything but brought it for the sake of man in all aspects of his life and in order to preserve the interests of the individual and society and what is in the interest and interest of the people, maintaining order, establishing justice and equity, repelling corruption and punishing criminals, corrupters and unjust, and for that Islamic law did not leave this crime unpunished, and it authorized the legal ruler to assess the punishment for this crime, and the crime of electronic extortion as the Shariah is held accountable for it. Also, the positive law did not leave the criminal unpunished.